Conflict and Peace Reportage in Nigeria Newspaper: A Reappraisal of Punch and Daily Trust Newspaper (January – July, 2019) - Paul Timileyin Aleyomi (Journal of Social Science, 2023)
Abstract This study investigates the coverage of conflict and peace issues in Nigerian newspapers, specifically focusing on Punch and Daily Trust. The research aims to achieve three primary objectives: assess the frequency of conflict and peace reportage in both newspapers, determine the level of prominence given to these issues by Punch and Daily Trust, and identify the categories under which such issues are reported. The study draws on the Agenda-Setting Theory and Framing Theory to provide a comprehensive analysis. Using a quantitative content analysis approach, the study examines stories related to conflict and peace issues published in the selected newspapers from January 2019 to July 2019. The key findings reveal distinct patterns in the reportage of conflict and peace matters. Punch exhibits a higher emphasis on certain categories like "Calamity/Killing," "Prevention," and "Warning," while Daily Trust places greater prominence on the "Call for Peace" theme. Moreover, the study unveils variations in the prominence given to different categories across the newspapers. The study concludes that the nuanced ways in which Punch and Daily Trust cover conflict and peace issues is based on their editorial decisions in shaping public awareness and discussions. Based on the study's outcomes, it is recommended that newspapers strategically consider their coverage of conflict and peace topics, fostering greater balance and comprehensive reporting. By adhering to these recommendations, newspapers can contribute to more informed public discourse on crucial societal matters.